2021
DOI: 10.1098/rsob.200369
|View full text |Cite
|
Sign up to set email alerts
|

Multiple nutritional phenotypes of fission yeast mutants defective in genes encoding essential mitochondrial proteins

Abstract: Mitochondria are essential for regulation of cellular respiration, energy production, small molecule metabolism, anti-oxidation and cell ageing, among other things. While the mitochondrial genome contains a small number of protein-coding genes, the great majority of mitochondrial proteins are encoded by chromosomal genes. In the fission yeast Schizosaccharomyces pombe , 770 proteins encoded by chromosomal genes are located in mitochondria. Of these, 195 proteins, many of which are impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…2021 ) and in the study of the conserved mechanisms affecting aging and lifespan ( Romila et al . 2021 ; Uehara et al . 2021 ; Mori et al .…”
Section: Introductionmentioning
confidence: 99%
“…2021 ) and in the study of the conserved mechanisms affecting aging and lifespan ( Romila et al . 2021 ; Uehara et al . 2021 ; Mori et al .…”
Section: Introductionmentioning
confidence: 99%
“…shk genes are apparently required for maintenance of cell viability in both proliferating and quiescent cells, whereas gze genes are essential only in quiescent cells. 40 shk genes and 85 gze genes have been so far identified (Hayashi et al, 2018; Nakazawa et al, 2018; Sajiki et al, 2009; Sajiki et al, 2018; Uehara et al, 2021). As diverse molecular roles of these gene products are predicted from annotations in POMBASE (https://www.pombase.org), a wide variety of molecules function together to enable cells to enter or exit G0 phase.…”
Section: Introductionmentioning
confidence: 99%
“…From a genome-wide analysis of genes essential for cell viability [ 13 ], one of the most striking differences between S. cerevisiae and S. pombe is the number of essential chromosomal genes related to mitochondrial function. For example, 96 essential S. pombe genes are required for translation of genes encoded in mtDNA, whereas only six budding yeast orthologues are essential [ 14 ]. Mitochondrial genome organization [ 11 , 15 ] in higher eukaryotic organisms is similar to that of S. pombe ; therefore, S. pombe mitochondria may serve as a useful model.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with descriptions in the fission yeast genome database (Pombase, [ 16 ]), comprehensive protein localization analysis [ 17 ] showed that 770 fission yeast proteins comprising approximately 15% of all proteins encoded by the genome are thought to be located in mitochondria and/or to possess mitochondrial functions. As discussed in our previous study [ 14 ], approximately 25% of them (195 proteins) are required for cell survival in vegetative conditions.…”
Section: Introductionmentioning
confidence: 99%